2007
DOI: 10.1007/s12043-007-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of Cr layer coated on TiNi films for hydrogen absorption

Abstract: The effect of hydrogen absorption on electrical resistance with temperature for TiNi and TiNi-Cr thin films was investigated. The TiNi thin films of thickness 800 A were deposited at different angles (θ = 0 • , 30 • , 45 • , 60 • and 75 • ) under 10 −5 Torr pressure by thermal evaporation on the glass substrate at room temperature. A layer of Cr of thickness 100Å was coated on the TiNi thin films. The changing rate of hydrogen absorption increases after Cr layer coating because Cr enhances the catalytic proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…In addition to solar cells, DSG nanostructures were also utilized as photoelectrodes for solar water splitting. Wolcott et al (2009) demonstrated a 0.1% photo-to-hydrogen efficiency with OAD TiO 2 nanorods, and they further showed that TiO 2 -WO 3 core-shell nanorods could further extend the photoconversion to visible wavelength range (Smith et al, 2011). Other TiO 2 -based nanostructures, such as Cr doped (Larsen et al, 2011) and CdSe decorated (Larsen et al, 2012) TiO 2 nanorods, were explored as the photoelectrodes for water splitting.…”
Section: Composition Tunabilitymentioning
confidence: 99%
“…In addition to solar cells, DSG nanostructures were also utilized as photoelectrodes for solar water splitting. Wolcott et al (2009) demonstrated a 0.1% photo-to-hydrogen efficiency with OAD TiO 2 nanorods, and they further showed that TiO 2 -WO 3 core-shell nanorods could further extend the photoconversion to visible wavelength range (Smith et al, 2011). Other TiO 2 -based nanostructures, such as Cr doped (Larsen et al, 2011) and CdSe decorated (Larsen et al, 2012) TiO 2 nanorods, were explored as the photoelectrodes for water splitting.…”
Section: Composition Tunabilitymentioning
confidence: 99%
“…Basically, Ni(111) and a monolayer of Cr atoms on Ni(111)-Cr ML /Ni(111)-surfaces are used for this purpose. Alloying and multilayer formation of Ni to other metals are some of the possible solutions to improve its reactivity while solving the problem on degradation [15,16]. Cr electrodeposits have been proven and are used extensively to protect the base metal from corrosion [17].…”
Section: Introductionmentioning
confidence: 99%